Tunnelling control of chemical reactions : the organic chemist´s perspective - Ley, David; Gerbig, Dennis; Schreiner, Peter R.; Justus Liebig University Giessen (My University, 2012)
Even though quantum mechanical tunnelling has been appearing recurrently mostly in theoretical studies that emphasize its decisive role for many chemical reactions, it still appears suspicious to most organic chemists. Recent experiments in combination with powerful computational approaches, however, have demonstrated that tunnelling must be included to fully understand chemical reactivity. Here we provide an overview of the importance of tunnelling in organic chemical reactions.
Keywords: ddc:540